Análise de perdas técnicas em alimentadores de média tensão usando fluxo de carga monofásico e trifásico - Silva, Francisco Jeandson Rodrigues da (2019)
The electricity distributors have great financial losses caused by the electrical losses in their distribution networks. Therefore, it is important to develop simple and reliable solutions to minimize this economic impact. There are several computational tools to calculate the electrical losses based on two methodologies: the single-phase and three-phase load flow. In this work, initially, CEPEL's ANAREDE load flow is used to perform single-phase loss analysis in balanced distribution systems with average demand and border measurements. In order to use three-phase load flow, it is mandatory to obtain three-phase electrical data and, currently, there is no methodology developed for this purpose. Then, a new methodology for obtaining three-phase data for real distribution feeders was developed, with the following steps: extracting the electrical information (kW, kVAr and FP) from the online system; To analyze the behavior of the load curve of the feeders, to set up tables with the hourly means per phase; analyze the level of load unbalance of the feeders; construct a file with the three-phase data correcting the demands as measured from the monitoring system. The data obtained with the new methodology, together with the INTERPLAN program were used to calculate the technical losses in three-phase true feeders. With the results obtained from ANAREDE, it was possible to propose a project to reduce 94 MW of losses in real feeders. In the case of results obtained with INTERPLAN, it was possible to reduce the load unbalance of real feeders and to connect renewable sources, to obtain a reduction in the percentage of losses in two feeders of 31.93% and 73.32%, which corresponds to a savings of R $ 9,280 per month. Therefore, it is possible to affirm that the analysis of technical losses performed using the average demands and the border measurements obtained satisfactory results, that the new methodology for obtaining three-phase data of distribution systems can be used in the electric sector, providing the use of any threephase load flow, for the reduction of electrical losses with the reduction of load unbalance.